2011
DOI: 10.1007/s00586-011-1751-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of neurological scoliosis using hybrid construct (lumbar transpedicular screws plus thoracic sublaminar acrylic loops)

Abstract: In the nineties, most spinal surgeons supported the validity of segmental spine instrumentation, but this procedure has progressively been abandoned because difficult and with a high risk of neurological complications, in favor of the Cotrel-Dobousset (CD). The CD instrumentation is based on segmentation of curves, thus improving the angular correction and actuates sagittal profile. Sublaminar acrylic loops (Universal Clamp) shows the same resistance to stress as steel or titanium alloy sublaminar wires. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…The promising intermediate-term safety results of sublaminar UCs are in contrast to the intermediate-term safety issues of sublaminar wiring [17][18][19]. La Rosa et al also noted the safety of UCs used in hybrid constructs with thoracic hooks and lumbar pedicle screws in a series of 15 patients with neurological scoliosis greater than 100°and an average followup of 3 years [20]. An apparent superiority in both intraoperative and intermediate-term safety of UCs compared to sublaminar wires has also been discussed by spinal surgeons who reported the use of UCs in the thoracic spine for traumatic vertebral lesions [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The promising intermediate-term safety results of sublaminar UCs are in contrast to the intermediate-term safety issues of sublaminar wiring [17][18][19]. La Rosa et al also noted the safety of UCs used in hybrid constructs with thoracic hooks and lumbar pedicle screws in a series of 15 patients with neurological scoliosis greater than 100°and an average followup of 3 years [20]. An apparent superiority in both intraoperative and intermediate-term safety of UCs compared to sublaminar wires has also been discussed by spinal surgeons who reported the use of UCs in the thoracic spine for traumatic vertebral lesions [21].…”
Section: Discussionmentioning
confidence: 99%
“…This confirmed an earlier study by Ilharreborde et al, who reported an average initial thoracic main curve correction from 60°pre-operatively to 20°(66% correction) in 75 AIS patients treated with UC hybrid constructs and a subsequent loss of only 2°(3%) at the 2-year follow-up [13]. In the series of 15 patients with more severe, neurological scoliosis[100°, La Rosa et al achieved a 70% initial reduction (from 107 to 32°) and lost only 7°of correction after an average follow-up of 3 years [20]. The intermediate-term results reported here on the corrective efficacy of the UC in the coronal plane are not inferior to results observed with other spinal anchors that have known safety issues [2,[22][23][24][25][26][27]].…”
Section: Discussionmentioning
confidence: 99%
“…Mean radiation exposure time was 6 ± 1.5 s. We used a mean of six transpedicular screws (range 4-11), seven UC (range 5-9) and five hooks (range 4-6). Results and complications have been described in detail in the previous report [10]. Concerning post-operative thoracic kyphosis, the authors noted that it is not possible to define a clear percentage of correction, in absence of an actual range of ''normal value''.…”
Section: Resultsmentioning
confidence: 96%
“…The Universal Clamp is characterized by three components: a woven polyester band (Dacron), a titanium alloy (or stainless steel) clamp and a locking screw (titanium alloy or stainless steel). The surgical technique has already been described in previous study [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation